Childrens Safety Education Model through Child-Friendly Games - Widowati, Evi; Hendriyani, Rulita; Nugroho, Efa; Qin, Axel Lee Wye (KEMAS: Jurnal Kesehatan Masyarakat, 2018)
Children are vulnerable to potential hazards from their environment because of their cognitive, psychological and social developments are in immature stages. Formal education is still lacking in teaching safety concepts for children, hence a fun educational media for children is needed so that children can learn through child-friendly educative games. Because of that develop a fun child safety education model is important to improve childrens knowledge on the importance of safety, so that children can easily understand how to implement safety values in their life. We used Research and Development (RD) level 1 design to develop childrens safety education game, which consisted of five stages, started from the data collection up to assess the product effectiveness. The result was a â€œsnake and ladders of safetyâ€ game as safety education media for children. We presented 12 pictures in â€œsnake and ladders of safetyâ€ game. This research was conducted on year 2017. Based on the game evaluation, the highest average pretest score was 37.9 and the average posttest score increased to 65.5, hence there was an increase of knowledge on safety by 73.1%. It can be concluded that this game can increase childrens knowledge on safety.